Cartilage damage and bone erosion are more prominent determinants of functional impairment in longstanding experimental arthritis than synovial inflammation - Hayer, Silvia (Dis Model Mech, 2016)
Chronic inflammation of articular joints causing bone and cartilage destruction consequently leads to functional impairment or loss of mobility in affected joints from individuals affected by rheumatoid arthritis (RA). Even successful treatment with complete resolution of synovial inflammatory processes does not lead to full reversal of joint functionality, pointing to the crucial contribution of irreversibly damaged structural components, such as bone and cartilage, to restricted joint mobility. In this context, we investigated the impact of the distinct components, including synovial inflammation, bone erosion or cartilage damage, as well as the effect of blocking tumor necrosis factor (TNF) on functional impairment in human-TNF transgenic (hTNFtg) mice, a chronic inflammatory erosive animal model of RA. We determined CatWalk-assisted gait profiles as objective quantitative measurements of functional impairment. We first determined body-weight-independent gait parameters, including maximum intensity, print length, print width and print area in wild-type mice. We observed early changes in those gait parameters in hTNFtg mice at week 5 – the first clinical signs of arthritis. Moreover, we found further gait changes during chronic disease development, indicating progressive functional impairment in hTNFtg mice. By investigating the association of gait parameters with inflammation-mediated joint pathologies at different time points of the disease course, we found a relationship between gait parameters and the extent of cartilage damage and bone erosions, but not with the extent of synovitis in this chronic model. Next, we observed a significant improvement of functional impairment upon blocking TNF, even at progressed stages of disease. However, blocking TNF did not restore full functionality owing to remaining subclinical inflammation and structural microdamage. In conclusion, CatWalk gait analysis provides a useful tool for quantitative assessment of functional impairment in inflammatory destructive arthritis. Our findings indicate that cartilage damage and bone erosion, but not synovial inflammation, are the most important determinants for progressive functional impairment in this chronic erosive arthritis model.